2017
DOI: 10.1038/bmt.2017.222
|View full text |Cite
|
Sign up to set email alerts
|

Foiling fungal disease post hematopoietic cell transplant: review of prophylactic strategies

Abstract: Hematopoietic cell transplantation (HCT) offers definitive management for a wide variety of malignant and nonmalignant diseases. Conditioning regimens and therapies used to prevent and treat GvHD are immune suppressive, often increasing the risk of developing fungal disease due to yeasts or molds. Antifungal prophylaxis may be useful in preventing morbidity and mortality during and after HCT. In this article, we review the epidemiology and current literature regarding strategies for prevention of invasive fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Patients with hematologic malignancies are at high risk of developing invasive fungal disease (IFD). The highest incidences have been reported in allogeneic hematopoietic cell transplant (HCT) recipients and in patients with acute myeloid leukemia (AML) receiving induction remission chemotherapy [1][2][3][4][5][6]. In addition, recent studies have shown a high incidence of IFD in patients with acute lymphoid leukemia (ALL) [7,8], and the emergence of a new group at risk: patients with chronic lymphoproliferative diseases receiving ibrutinib [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with hematologic malignancies are at high risk of developing invasive fungal disease (IFD). The highest incidences have been reported in allogeneic hematopoietic cell transplant (HCT) recipients and in patients with acute myeloid leukemia (AML) receiving induction remission chemotherapy [1][2][3][4][5][6]. In addition, recent studies have shown a high incidence of IFD in patients with acute lymphoid leukemia (ALL) [7,8], and the emergence of a new group at risk: patients with chronic lymphoproliferative diseases receiving ibrutinib [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…During the pre-engraftment period, the risk for IMI is elevated due to profound neutropenia. 3 Combined with the possibility that high-risk patients with AML or MDS may not have received adequate anti-mold prophylaxis prior to allo-HSCT at our institution, it is not surprising that our results showed a high frequency of IMI during pre-engraftment.…”
Section: Discussionmentioning
confidence: 59%
“…4 While IMI carries a significant risk for mortality, the routine use of mold-active agents for prophylaxis remains a subject of debate. 3,6,20 In this study, patients received antifungal prophylaxis with micafungin followed by fluconazole, with the option to escalate to voriconazole in patients receiving corticosteroids for GVHD. The incidence rate of proven or probable IMI during the study period was 18.4 cases per 100 patient-years, with a one-year cumulative incidence of 14%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations